Типологія народних співців – озанів, описаних у «Книзі Деде Коркута», та їх роль у творенні ашикської традиції на території Туреччини - Алі Якиджи (Народна творчість та етнографія, 2010)
The bardic poetry tradition and bards have had an important place in history of culture. Bards have a significant role in creating epics taking strength from mythology during the history and they have an influence on the social, political, cultural and religious life of the society that they live in. This rooted tradition have been able to stay alive and it is transferred to our age with its influences. Today, this tradition is called «minstrel tradition». Dede Korkut Kitabı is one of the primary sources where the transformations of the tradition can be traced. In this paper, the roles, the missions and contexts of the bards mentioned in Dede Korkut Kitabı are analyzed according to these transformations.